Purification and Characterization of Prolyl Hydroxylase 3/Pyruvate Kinase Isoform 2 Protein Complex. - Kumar,S; Patel,AK (Mol Biotechnol, 2020)
The prolyl hydroxylase 3 (PHD3) protein is less abundant in normal oxygen conditions (normoxia) but increases under deficient oxygen condition (hypoxia). Since cancerous cells often thrive in hypoxic conditions and predominantly express the Pyruvate kinase isoforms 2 (PKM2), the PHD3/PKM2 interaction might be particularly important in cancer development. In the present study, the PHD3/PKM2 complex was co-expressed and purified by size-exclusion chromatography. The interaction of PHD3 with PKM2 was confirmed in Native gel as well as western blot analysis. The PHD3/PKM2 complex formed discreet crystals under suitable conditions, and diffraction data revealed that crystal belonged to the P1 space group with 3.0 Å resolution. This is the first crystal report of PHD3/PKM2 complex as well as this study demonstrates a direct physical binding through protein-protein interaction. The structural analysis of complex will provide the information regarding the amino acid residues critical for the catalytic mechanism. Based on the structural information thus obtained, pharmacological interference with the PHD3/PKM2 interaction could be used as a novel strategy to reduce the cancer progression.